Fine-Tuning of PGC1α Expression Regulates Cardiac Function and Longevity. Issue 7 (13th September 2019) - Zhu, Xudong; Shen, Weiyan; Yao, Ke; Wang, Hu; Liu, Bo; Li, Tangliang; Song, Lijuan; Diao, Daojun; Mao, Genxiang; Huang, Ping; Li, Chengtao; Zhang, Hongbo; et al.
Abstract : Rationale: PGC1α (peroxisome proliferator-activated receptor gamma coactivator 1α) represents an attractive target interfering bioenergetics and mitochondrial homeostasis, yet multiple attempts have failed to upregulate PGC1α expression as a therapy, for instance, causing cardiomyopathy. Objective: To determine whether a fine-tuning of PGC1α expression is essential for cardiac homeostasis in a context-dependent manner. Methods and Results: Moderate cardiac-specific PGC1α overexpression through a ROSA26 locus knock-in strategy was utilized in WT (wild type) mice and in G3Terc −/− (third generation of telomerase deficient; hereafter as G3) mouse model, respectively. Ultrastructure, mitochondrial stress, echocardiographic, and a variety of biological approaches were applied to assess mitochondrial physiology and cardiac function. While WT mice showed a relatively consistent PGC1α expression from 3 to 12 months old, age-matched G3 mice exhibited declined PGC1α expression and compromised mitochondrial function. Cardiac-specific overexpression of PGC1α (PGC1α OE ) promoted mitochondrial and cardiac function in 3-month-old WT mice but accelerated cardiac aging and significantly shortened life span in 12-month-old WT mice because of increased mitochondrial damage and reactive oxygen species insult. In contrast, cardiac-specific PGC1α knock in in G3 (G3 PGC1α OE ) mice restored mitochondrial homeostasis and attenuated senescence-associated secretory phenotypes, thereby preserving cardiac performance with age and extending health span. Mechanistically, age-dependent defect in mitophagy is associated with accumulation of damaged mitochondria that leads to cardiac impairment and premature death in 12-month-old WT PGC1α OE mice. In the context of telomere dysfunction, PGC1α induction replenished energy supply through restoring the compromised mitochondrial biogenesis and thus is beneficial to old G3 heart. Conclusions: Fine-tuning the expression of PGC1α is crucial for the cardiac homeostasis because the balance between mitochondrial biogenesis and clearance is vital for regulating mitochondrial function and homeostasis. These results reinforce the importance of carefully evaluating the PGC1α-boosting strategies in a context-dependent manner to facilitate clinical translation of novel cardioprotective therapies. Abstract : Supplemental Digital Content is available in the text.